Možnosti in omejitve zvočnih zapisov ljudske glasbe - Kunej, Drago (Traditiones (Ljubljana), 2000)
Audio recording of music denotes a giant step forward in recording music. It strongly influenced the production and reception of music and the manner in which it was spread among people. Yet despite thgis, almost ideal, manner of preserving sound audio recording to this very day remains but a way of recording music which aside from many advantages also has its limitations, regardless of the rapid technical development and progress in audio recording. This is especially true of documentary recordings of folk music in the field; such recording are by no means a clear source of sound information, but acquire their true value only if one considers the circumstances in which they had been recorded, and the enclosed technical documentation
Keywords: zvočni zapisi; etnomuzikologija; folk music; ljudska glasba